2012
DOI: 10.1007/s10120-011-0127-0
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive epidemiology of gastric adenocarcinoma in the State of Texas by ethnicity: Hispanic versus White non-Hispanic

Abstract: The incidence of gastric adenocarcinoma is higher in Hispanics than in Whites in both El Paso County and the remaining portion of Texas. Hispanics have a higher grade of gastric adenocarcinoma. The prevalence of late stage at the time of diagnosis is higher in younger patients than in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 41 publications
(38 reference statements)
1
20
1
Order By: Relevance
“…Studies with data from U.S. hospitals and SEER reviews show that in general, Hispanics have more distal type cancer than non-Hispanic Whites [14,15,18]. In addition, most distal incident cases were found in the antrum in Central America, whereas cancer of the corpus was slightly more frequent among U.S. Hispanics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with data from U.S. hospitals and SEER reviews show that in general, Hispanics have more distal type cancer than non-Hispanic Whites [14,15,18]. In addition, most distal incident cases were found in the antrum in Central America, whereas cancer of the corpus was slightly more frequent among U.S. Hispanics.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer incidence rates for Hispanics in the U.S. are nearly double those of whites [13]. In addition, Hispanics have more distal type cancer than non-Hispanic Whites [14,15]. Interestingly, recent studies suggest an increase in diffuse cancer in foreign born Hispanic men and U.S. born Hispanic women [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data from the Surveillance Epidemiology and End Results (SEER) Program showed that the gastric cancer incidence rate for Hispanics in the United States is double that of Caucasians and gastric cancer is the seventh leading cause of cancer death in this population. Hispanic patients with gastric cancer tend to present with more advanced disease, diffuse‐type and signet ring cell histology, and linitis plastica relative to Caucasian patients …”
Section: Introductionmentioning
confidence: 99%
“…Hispanic patients with gastric cancer tend to present with more advanced disease, diffuse-type and signet ring cell histology, and linitis plastica relative to Caucasian patients. 3,9 In addition to having a distinct clinical profile, Hispanic patients with gastric cancer face unique challenges in access to care. This is particularly true for undocumented immigrants who cannot afford or are not eligible for insurance.…”
mentioning
confidence: 99%